THE ANALYSIS OF REPETITION DRILL TECHNIQUE IN TEACHING ENGLISH VOCABULARY TO VOCATIONAL HIGH SCHOOL STUDENTS - Rahma Annisa; Mohammad Fatoni; Moh Zainuddin; Rahma Annisa; Mohammad Fatoni; Moh Zainuddin (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
Based on the Indonesian education system, English is one of the subjects that must be taught in every institution and teaching English in Indonesia is not easy, it will be more difficult than other subjects because there are many students who lack experience with English so it will be difficult for students to understand. Teachers must find ways to make students excited and motivated to learn English. Researchers conducted pre-observations at Al Kyai Vocational School and found that repetition drills can improve English and increase concentration. This study aims to analyze repetition exercises in teaching English and the motivation teachers give to students. The research was conducted in collaboration with eleventh grade English teacher at SMK Al Kyai Bojonegoro. The results showed that evaluation of repetition drills included vocabulary, pronunciation, sentence structure, and dialogue exercises. The motivation given to students had both positive and negative effects. Keywords: Analysis, Repetition drill, Teaching English, Students.